Kesejahteraan Masyarakat Pasca Pemekaran Desa (Studi pada Desa Sumberbrantas, Kota Batu) - Huda, A. Faisal Yusni (Jurnal Administrasi Publik, 2014)
Abstract: Public Welfare after Village Proliferation. The number of village growth, from year to year hade showing a significant increase from year to year showed a significant increase. From 2007 through 2012 as many as 4793 a growing number of rural villages, one reason is the high village Proliferation proposal. Since the enactment of Government Regulation No. 72 Year 2005 on the Village implications for the increasing demands of village Proliferation. The main purpose of village proliferation is for the public welfare. This study seeks to analyze the welfare of rural communities after Proliferation and the factors that influence it.. The public welfare after proliferation village of the Sumberbrantas Village already showing good progress, due to the development of economic activity and adequate road infrastructure. Although it still needs to pay more attention to education and health services. Keywords: village proliferation, public welfare Abstrak: Kesejahteraan Masyarakat Pasca Pemekaran Desa. Pertumbuhan jumlah desa dari tahun ke tahun menunjukkan peningkatan yang signifikan. Sejak tahun 2007 hingga tahun 2012 pertumbuhan jumlah desa sebanyak 4793 desa, salah satu penyebabnya adalah tingginya usulan pemekaran desa. Sejak diundangkannya Peraturan Pemerintah Nomor 72 Tahun 2005 tentang Desa berimplikasi pada meningkatnya tuntutan pemekaran desa. Tujuan utama pemekaran desa adalah untuk mensejahterakan masyarakat. Penelitian ini berusaha menganalisis kesejahteraan masyarakat pasca pemekaran desa dan faktor-faktor yang mempengaruhinya. Kesejahteraan masyarakat Desa Sumberbrantas pasca pemekaran desa sudah menunjukkan progres yang baik dikarenakan mulai berkembangnya aktifitas ekonomi serta insfrastruktur jalan yang memadai. Walaupun demikian masih perlu perhatian lebih serius pada perbaikan layanan pendidikan dan kesehatan. Â  Kata kunci: pemekaran desa, kesejahteraan masyarakat